Systematic analysis of the transcriptome in small‐cell carcinoma of the oesophagus reveals its immune microenvironment. Issue 10 (5th October 2020) - Zhao, Qi; Chen, Yan‐Xing; Wu, Qi‐Nian; Zhang, Chao; Liu, Min; Wang, Ying‐Nan; Feng, Yan‐Fen; Hu, Jia‐Jia; Fu, Jian‐Hua; Yang, Hong; Qi, Jing‐Jing; Wang, Zi‐Xian; et al.
Abstract: Objectives: Although the genomic landscape of small‐cell carcinoma of the oesophagus (SCCE) has been dissected, its transcriptome‐level aberration and immune microenvironment status are unknown. Methods: Using ultra‐deep whole transcriptome sequencing, we analysed the expression profile of nine paired SCCE samples and compared the transcriptome with public transcriptomic data set of normal oesophageal mucosa and other cancer types. Based on the transcriptome data, the immune signatures were investigated. The genomic data of 55 SCCE samples were also applied for immune checkpoint blockade therapy (ICBT) biomarker evaluation including microsatellite instability (MSI) status, tumor mutation burden (TMB) and neoantigen burden (TNB). Also, we evaluated the CD8, CD68 and programmed death‐ligand 1 (PD‐L1) in 62 retrospective SCCE samples with IHC assay. Results: Differential expression analysis revealed that the cell cycle, p53, and Wnt pathways are significantly deregulated in SCCE. Immune microenvironment analysis showed that high leucocyte infiltration and adaptive immune resistance did occur in certain individuals, while the majority showed a relatively suppressive immune status. Immune checkpoints such as CD276 and LAG‐3 were upregulated, and higher M2 macrophage infiltration in tumor tissues. Furthermore, normal tissues adjacent to the tumors of SCCE presented a more activated inflammatory status than tumor‐free healthy controls. These observations showed that ICBT might benefit SCCE patients. As the critical biomarker of ICBT, TMB of SCCE was 3.64 with the predictive objective response rate 13.2%, while the PD‐L1‐positive rate was 43%. Conclusions: Our study systematically characterized the immune microenvironment in small‐cell carcinoma of the esophagus and provided evidence that several patients with SCCE may benefit from immune checkpoint blockade therapy. Abstract : In this study, transcriptomic aberrance and immune microenvironment of small‐cell carcinoma of the esophagus (SCCE) was comprehensively characterized with transcriptome and immunohistochemistry analysis. Assessment of immune checkpoint blockade (ICB) treatment biomarkers provides a rationale for use of ICB treatment in patients with SCCE.